EXPLORING WIDOW REMARRIAGE: A STUDY OF VEDIC INDIA - Rashid Manzoor Bhat; Dr. Lakmini Gamage (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
The study revisits the contentious issue of widow remarriage in Vedic India through an in-depth analysis of various passages from Vedic texts and different interpretations posited by scholars. The findings suggest that, while it has been historically viewed marriage as an indissoluble sacrament in Hinduism, evidence regarding widow remarriage is not conclusive. Some scholars argue that widow remarriage, specifically to a deceased husband's brother, was practiced during the Vedic era. This assertion is supported by Rigvedic passages X.18.8 and X.40.2, which purportedly hint at the practice. However, this interpretation is disputed, with some arguing that these passages actually underscore practices of self-sacrifice or 'niyoga' (levirate marriage). The study further explores Atharvavedic verses suggesting the remarriage of a punarbhu or a betrothed woman, not a widow. The research therefore suggests that Vedic texts did not explicitly endorse widow remarriage. It argues for a nuanced understanding of ancient customs and societal norms, highlighting the need for more rigorous and context-sensitive interpretations of Vedic texts.